2017
DOI: 10.31018/jans.v9i2.1351
|View full text |Cite
|
Sign up to set email alerts
|

Participatory rural appraisal and farmers’ perception about common bean varieties in temperate Kashmir

Abstract: Present investigation was undertaken during 2012 to 2014 in which 54 genotypes, both pole and bush type of Common beans (Phaseolus vulgaris) were selected among a number of germplasm lines, land races and research material in order to generate information on the farmer’s’ perception about the Common bean varieties. Participatory rural appraisal was conducted in 32 villages of Kashmir through a broad questionnaires comprising of questions pertaining to the socio-economic conditions, farming systems, production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The high market value (USD 800 per tonne) of navy beans compared to other subsistence crops such as maize prompts farmers to reserve less for household consumption in search of income. These findings contradict with Katungi et al [5], Sheikh et al [17], Asfaw et al [24], Njoki [33], and Balcha and Tigabu [43] who reported a significant number of farmers who preferred common bean cultivars with a good taste and short cooking duration in their studies. Farmers did not value the importance of invisible traits such as nutritional value (Fe and Zn) and canning quality probably due to the unfamiliarity with the nutritional and health benefits of consuming bio fortified cultivars in these two districts.…”
Section: Farmer's Trait Preferencesmentioning
confidence: 64%
See 1 more Smart Citation
“…The high market value (USD 800 per tonne) of navy beans compared to other subsistence crops such as maize prompts farmers to reserve less for household consumption in search of income. These findings contradict with Katungi et al [5], Sheikh et al [17], Asfaw et al [24], Njoki [33], and Balcha and Tigabu [43] who reported a significant number of farmers who preferred common bean cultivars with a good taste and short cooking duration in their studies. Farmers did not value the importance of invisible traits such as nutritional value (Fe and Zn) and canning quality probably due to the unfamiliarity with the nutritional and health benefits of consuming bio fortified cultivars in these two districts.…”
Section: Farmer's Trait Preferencesmentioning
confidence: 64%
“…Participatory rural appraisal (PRA) relies on participation of the community (local people) and considers the value of stakeholders' knowledge, skill, experience, their needs, preferences, abilities, and innovation [9]. Participatory rural appraisal has been extensively used to identify production constraints of many crops [10][11][12][13][14][15][16][17]. Ceccarelli et al [18] and Morris and Bellon [19] reported that the participation of farmers' in the initial breeding process provides insight into cultivar trait preferences, production and marketing constraints so that they can be addressed during the breeding process and hence enhance the adoption rate of newly developed cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Tolerance to storage weevils, grain taste and cooking traits were not considered as important traits for improvement because farmers grow navy beans for income generation, and also deliver most (90 %) of the produce to the contractor, prompting them not to value or put more weight on them. These ndings contradict with Katungi et al [5], Sheikh et al [17], Asfaw et al [24], Njoki [33], and Balcha and Tigabu [43] who reported a signi cant number of farmers who preferred common bean cultivars with a good taste and short cooking duration in their studies. Farmers did not value the importance of invisible traits such as nutritional value (Fe and Zn) and canning quality probably due to the unfamiliarity with the nutritional and health bene ts of consuming bio forti ed cultivars in these two districts.…”
Section: Farmer's Trait Preferencesmentioning
confidence: 65%
“…Tolerance to storage weevils, grain taste and cooking traits were not considered as important traits for improvement because farmers grow navy beans for income generation, and also deliver most (90%) of the produce to the contractor, prompting them not to value or put more weight on them. These ndings contradict with Asfaw et al [6], Balcha and Tigabu [10], Katungi et al [37], Njoki [51], and Sheikh et al [56] who reported a signi cant number of farmers who preferred common bean cultivars with a good taste and short cooking duration in their studies. Farmers did not value the importance of invisible traits such as nutritional value (Fe and Zn) and canning quality probably due to the unfamiliarity with the nutritional and health bene ts of consuming bio forti ed cultivars in these two districts.…”
Section: Farmer's Trait Preferencesmentioning
confidence: 67%
“…Participatory rural appraisal (PRA) relies on participation of the community (local people) and considers the value of stakeholders' knowledge, skill, experience, their needs, preferences, abilities, and innovation [18]. Participatory rural appraisal has been extensively used to identify production constraints of many crops [1,2,28,29,44,48,49,56]. Ceccarelli et al [17] and Morris and Bellon [45] reported that the participation of farmers' in the initial breeding process provides insight into cultivar trait preferences, production and marketing constraints, so that they can be addressed during the breeding process and hence enhance the adoption rate of newly developed cultivars.…”
Section: Introductionmentioning
confidence: 99%